2022
DOI: 10.3390/ijms23084303
|View full text |Cite
|
Sign up to set email alerts
|

YY2 Promotes Osteoblast Differentiation by Upregulating Osterix Transcriptional Activity

Abstract: Yin Yang 2 (YY2) is a paralog of YY1, a well-known multifunctional transcription factor containing a C-terminal zinc finger domain. Although the role of YY1 in various biological processes, such as the cell cycle, cell differentiation and tissue development, is well established, the function of YY2 has not been fully determined. In this study, we investigated the functional role of YY2 during osteoblast differentiation. YY2 overexpression and knockdown increased and decreased osteoblast differentiation, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
2
2
0
Order By: Relevance
“…A recent study has validated that Yy2 could promote osteoblast differentiation by upregulating transcriptional activity of Osterix in BMP4-induced C2C12 cells. 39 Consistently, we detected significantly lower expression of Yy2 in osteoporosis mice and experimentally verified putative contributory roles of YY2 in promoting human osteoblast differentiation. The roles of YY2 in chromatin organization are currently unknown.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A recent study has validated that Yy2 could promote osteoblast differentiation by upregulating transcriptional activity of Osterix in BMP4-induced C2C12 cells. 39 Consistently, we detected significantly lower expression of Yy2 in osteoporosis mice and experimentally verified putative contributory roles of YY2 in promoting human osteoblast differentiation. The roles of YY2 in chromatin organization are currently unknown.…”
Section: Discussionsupporting
confidence: 79%
“…We noted that many enriched TFs had known roles in osteoblast differentiation or bone metabolism ( Figure 4 A; Table S13 ), such as HOXC10, 37 MEF2A, 38 or YY2. 39 Consistently, GO biological process enrichment analysis revealed that enriched TFs were significantly enriched for several bone-relevant pathways including skeletal system development and ossification ( Figure 4 C). To further explore putative roles in osteoblast differentiation for enriched TFs, we compared their expression change in differentiated osteoblast for different time points (0.5–96 h) against non-differentiated cells ( Table S1 ), 40 and we detected 10 TFs (CPEB1, ETS1, FOXC2, FOXD2, HOXC10, MEF2A, NFE2L3, SMAD4, SOX9, and YY1) with significantly changed expression (FDR < 0.05, Table S14 ).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The previous study also showed the differentiation of OB via upregulating RUNX2 34,35 and OSX's role as an inducer. 30,36 The increase of OB is followed by increasing OCN. OCN may function as a matrix signal in the recruitment and differentiation of bone-resorbing cells.…”
Section: Discussionmentioning
confidence: 99%